2013
DOI: 10.17795/jhealthscope-9833
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Volatile Organic Compounds on Fluidized Activated Carbon Bed

Abstract: Background: Fixed bed adsorber as a controlling method for volatile organic compounds is widely used. However, these adsorbers are facing some issues such as high pressure drop, non-uniformed distribution of fluid, channeling and blockage. Fluidized bed adsorber as a novel method solves lots of these limitations. Objectives: This research aimed at investigating factors affecting the adsorption of vapors of VOCs on fluidized bed adsorbers. Materials and Methods: To assess adsorption, an annular fluidized bed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In the adsorption process, molecules physically adsorb to the adsorbent and separate from the gas stream. When all the pores of the adsorbent are filled, it is unable to adsorb more contaminant (41). Zhang et al found that with increasing contact time, the SO 2 removal efficiency by CaO as desulfurizers decreased; this is similar to the results of the current study (42).…”
Section: Discussionsupporting
confidence: 87%
“…In the adsorption process, molecules physically adsorb to the adsorbent and separate from the gas stream. When all the pores of the adsorbent are filled, it is unable to adsorb more contaminant (41). Zhang et al found that with increasing contact time, the SO 2 removal efficiency by CaO as desulfurizers decreased; this is similar to the results of the current study (42).…”
Section: Discussionsupporting
confidence: 87%
“…It has been used for a long time and is still used today as a successful adsorbent to remove pollutant gases and vapors [2,44,53]. Thus, RE of as high as 100% can be obtained with the good design of the reactor and appropriate amount of carbon granules [54,55]. But, the main drawback with the bare GAC is breakthrough and adsorbent saturation over time as observed obviously in this study.…”
Section: Photocatalytic Performancementioning
confidence: 72%
“…ere are three levels of this problem handling source, ventilation, and air cleaning. Several methods have been reported to control VOCs in the indoor environment such as toluene adsorption using activated carbon [15,23], catalytic or UV methods [22], an additive in foam formulation [17], thermal oxidation, and bio-treatment [13,14] methods. Every method comes with its advantages and limitations that should be considered based on individual indoor conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, VOCs can be controlled at source (during the manufacturing of the indoor product), ventilation, and air-cleaning [12]. e reported methods for air-cleaning include botanical puri cation, Catalytic combustion, Membrane Separation, Zeolite based adsorption, Bio-ltration, Absorption, and activated carbon-based adsorption [13][14][15]. Every method has its advantages and disadvantages, and the best suitable method can vary from site to site.…”
Section: Introductionmentioning
confidence: 99%